1989
DOI: 10.1177/002248718904000610
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Preferences for Training and Compensation for Field Supervision

Abstract: Despite the importance placed on qual ity field experiences in teacher prepara tion, little attention has been focused on optimal training and compensation for cooperating teachers who supervise student teachers. In a time of increasing expectations for supervisors and diminishing resources for colleges/ universities, the most meaningful and cost-effective forms of training and rewards must be identified to support the efforts of field-site personnel. Korinek presents and discusses the results of original and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Orland (2001) concluded in her study of mentor teachers as teacher educators, 'learning to become a mentor is a conscious process … and does not emerge naturally from being a good teacher' (75). In Korinek's (1989) study, cooperating teachers reported that they would like more preparation for supervision. Teachers who have been trained 'provided a more stable field experience, more specific feedback, and a more positive affective experience' (Wheeler 1989, cited in Guyton andMcIntyre 1990, 520).…”
Section: Discussionmentioning
confidence: 99%
“…Orland (2001) concluded in her study of mentor teachers as teacher educators, 'learning to become a mentor is a conscious process … and does not emerge naturally from being a good teacher' (75). In Korinek's (1989) study, cooperating teachers reported that they would like more preparation for supervision. Teachers who have been trained 'provided a more stable field experience, more specific feedback, and a more positive affective experience' (Wheeler 1989, cited in Guyton andMcIntyre 1990, 520).…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge base goes beyond "being a friend"; it requires that a mentor-mentee relationship develops -a trust relationship that focuses on learning about teaching and learning. Cooperating teachers appear to have the greatest influence on a student teacher's professional development (Guyton, 1989;Karmas & Jacko, 1977;Korinek, 1989;McIntyre, 1984), yet they are generally unprepared for the task of supervision (Grimmitt & Ratzlaff, 1986;Lewis, 1990).…”
Section: Supervision Training For Mentoringmentioning
confidence: 99%
“…According to Kornick (1989), cooperating teachers take on student teachers for a variety of reasons. Many feel a sense of professional obligation and see the opportunity as a chance to revitalize their teaching.…”
Section: Literature On Failure In Education Practicumsmentioning
confidence: 99%